what remains washes away - Tormann, Nora, 1992- (2019)
what remains washes away by Nora Tormann is the graduation work from the Department of Performing Arts at Iceland University of the Arts. Bodies are messy, bodies are lustrous, bodies are sensual, bodies are wise, bodies are complex, bodies are in constant change. Bodies fall apart. As ideological emplacements, they fall into aesthetic norms, gendering, and racialization of the flesh. They fall into the chasms of their materiality and the environments they move through. They fall into gaze. And yet, they keep falling out of gaze; subject to their logic they fragment and liquefy their reality and fiction, the inscriptions they carry. what remains washes away started as an exploration of the fluid relationship between a physical body and the social space within which it moves. It went on searching for spaces in which the body can do in being undone. what remains washes away invites into a liquid landscape, a space in which a female body meanders between exposure/exhaustion and refusal/regeneration. Celestial Bodies is a collection of reflections upon the pratcices of 7 artists. They are cotextualizing their work, expanding upon it, putting it into question. The video is protected with a password due to sensitive content. Please contact the artist for permission.